2019
DOI: 10.1111/mmi.14252
|View full text |Cite
|
Sign up to set email alerts
|

The developmental regulator MtrA binds GlnR boxes and represses nitrogen metabolism genes inStreptomyces coelicolor

Abstract: Summary In Streptomyces, GlnR is an activator protein that activates nitrogen‐assimilation genes under nitrogen‐limiting conditions. However, less is known regarding the regulation of these genes under nitrogen‐rich conditions. We determined that the developmental regulator MtrA represses nitrogen‐assimilation genes in nitrogen‐rich media and that it competes with GlnR for binding to GlnR boxes. The GlnR boxes upstream of multiple nitrogen genes, such as amtB, were confirmed as MtrA binding sites in vitro by e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(90 citation statements)
references
References 45 publications
8
82
0
Order By: Relevance
“…Recently, it was experimentally demonstrated that MtrA binds to one of the three putative GlnR binding sequences upstream of the amtB-glnK-glnD cluster (Zhu et al, 2019). Previously, three putative GlnR binding sites (named a1-b1, a2-b2, and a3-b3), each consisting in two binding repeats had been identified in the amtB promoter region (Wang et al, 2012;Li et al, 2018).…”
Section: Role Of the Two Components System Mtrab In Nitrogen Metabolimentioning
confidence: 99%
See 4 more Smart Citations
“…Recently, it was experimentally demonstrated that MtrA binds to one of the three putative GlnR binding sequences upstream of the amtB-glnK-glnD cluster (Zhu et al, 2019). Previously, three putative GlnR binding sites (named a1-b1, a2-b2, and a3-b3), each consisting in two binding repeats had been identified in the amtB promoter region (Wang et al, 2012;Li et al, 2018).…”
Section: Role Of the Two Components System Mtrab In Nitrogen Metabolimentioning
confidence: 99%
“…Previously, three putative GlnR binding sites (named a1-b1, a2-b2, and a3-b3), each consisting in two binding repeats had been identified in the amtB promoter region (Wang et al, 2012;Li et al, 2018). More recently, Zhu et al (2019) showed that the developmental regulator MtrA recognizes the a3-b3 binding sequence which also binds GlnR efficiently. This was confirmed by EMSA DNA binding assays using the a3-b3 sequence as probe (Figure 2).…”
Section: Role Of the Two Components System Mtrab In Nitrogen Metabolimentioning
confidence: 99%
See 3 more Smart Citations